Do Online Privacy Concerns Predict Selfie Behavior among Adolescents, Young Adults and Adults? - Dhir, Amandeep; Torsheim, Torbjørn; Pallesen, Ståle; Andreassen, Cecilie S. (Frontiers in Psychology, 2017)
Selfies, or self-portraits, are popularly taken and shared on social media for online self-presentation reasons, which are considered important for the psychosocial development and well-being of young people in today’s culture. Despite the growing popularity and widespread sharing of selfies in the online space, little is known about how privacy concerns moderate selfie behavior. In addition to this, it is also not known whether privacy concerns across age and gender groups influence selfie behavior. To address this timely issue, a survey assessing common selfie behaviors, i.e., frequency of taking (individual and group selfies), editing (cropping and filtering), and posting selfies online; and social media privacy concerns (over personal data being accessed and misused by third parties) was conducted. The web-survey was administrated to 3,763 Norwegian social media users; mean age of the sample was 27.79 years (SD=10.05, range 13 to 50 years), with a preponderance of women (n=2,509, 66.7%). The present study investigated the impact of privacy concerns on selfie behaviors across gender and age groups (adolescent, young-adult, adult) by use of structural equation modelling approach. Results suggest that young adults possess higher privacy concerns compared to adolescents and adults. Females possess higher privacy concerns than males. Higher privacy concerns among female social media users was linked to lower engagement in selfie behavior, but privacy concerns did not influence selfie behavior in the case of male adolescents and young adults. The study concludes with various theoretical and practical implications for both scholars and policy makers.